Breeding Sorghum [Sorghum Bicolor (L.) Moench] for High Quality Stover for Niger - Diakite, O.S. (University of Ghana, 2018)
Pasture shortage during March to July is the main constraint in cattle productivity in Niger. To alleviate this pasture shortage, farmers use dual purpose sorghum varieties where the grain is used as food and the nutritionally low quality stover as feed for their cattle during dry season. Consequently, cattle productivity is reduced. One sustainable means is to pave the way for better stover quality availability through incorporation of the brown midrib trait, which is known to improve quality of stover, into sorghum varieties. The main objective of this study was to develop dual purpose sorghum lines with high quality stover for sustained livestock productivity. The specific objectives were to (1) identify farmers’ and stover traders’ preferences on sorghum stover varieties; (2) introgress brown midrib6 and brown midrib12 genes in two Nigerien elite sorghum lines; (3) determine the agronomic and nutritive potential of new brown midrib (bmr) derived lines and (4) identify Single Nucleotide Polymorphism (SNP) mutations in Ethly methanesulfonate (EMS) sorghum mutants used in the national sorghum improvement programme. A Participatory Rural Appraisal (PRA) consisting of focus group discussions followed by semi-structured interviews, was conducted in three agro-ecological areas in Niger. Two bmr genes (bmr6 and bmr12) from three donor parents were introgressed into two Nigerien recurrent parents using hand emasculation in Sotuba, Mali. Ninety-four (94) derived BC1F3 families plus 6 checks were phenotyped using alpha lattice design in two sites (Tillabery and Konni) in Niger in 2017 rainy season. Selected derived families’ chemical compositions were analyzed at Sotuba Animal Nutrition Laboratory (LNA) in 2018 in Mali. Ten (10) EMS mutated accessions out of 554 phenotyped in Niger, were sequenced for candidate SNP discovery in Purdue University in 2018. PRA results revealed that farmers cultivated sorghum for dual purpose (grain and stover) with high preference for sorghum stover compared to pearl millet for cattle feeding. Farmers complained of feed shortage during dry season coupled with poor quality of their millet and sorghum stovers. Stover trading was a growing business despite the traditional poor management practices. Main criteria for forage quality traits were higher biomass, juiciness, stay-green for both farmers and traders. There were significant to highly significant differences among bmr derived families for grain and dry matter yield potential within and across sites. Grain yield ranged from 3271.2 kg/ha to 1205.4 kg/ha while dry matter yield varied from 6909.8 kg/ha to 2867.0 kg/ha. Significant variations were observed for the dry matter, Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and Acid Detergent Lignin (ADL) contents between parental and derived lines. Results from 10 EMS lines revealed bmr2, bmr6, bmr12 and stacked bmr2/bmr6 genotypes. No candidate SNP was found for 2 EMS mutants for the known bmr genes suggesting that these could represent new mutations. Further investigations may identify the nature of their candidate mutations. Deeper phenotyping on field and nutritional values are essential to detect higher yielding lines to confirm the already interesting data collected during the course of this study for improved cattle production in Niger.
PhD.
Keywords: Sorghum; Sorghum Bicolor (L.) Moench; Stover; Niger